2022
DOI: 10.1039/d2cc00956k
|View full text |Cite
|
Sign up to set email alerts
|

Amorphous palladium-based alloy nanoparticles as highly active electrocatalysts for ethanol oxidation

Abstract: Amorphous Pd-P metal-metalloid alloy nanoparticles showed higher electrochemical ethanol oxidation reaction performance than the crystalline Pd nanopartilces. The high performance was attributed to the rich defective coordination unsaturated sites and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…50 These characteristics make the amorphous phase unique in catalysis. For example, Zhang et al 62 reported palladium-based amorphous alloy nanoparticles for efficient EOR. Wang et al 63 synthesized Pd/C decorated on amorphous NiCo 2 O 4 as a highly active electrocatalyst for the EOR.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…50 These characteristics make the amorphous phase unique in catalysis. For example, Zhang et al 62 reported palladium-based amorphous alloy nanoparticles for efficient EOR. Wang et al 63 synthesized Pd/C decorated on amorphous NiCo 2 O 4 as a highly active electrocatalyst for the EOR.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…These results indicate that the presence of phosphorus atoms can affect the electronic structure of palladium atoms, making the palladium atom lose some electrons. The lost electrons for palladium will enhance the adsorption of OH, thereby promoting the catalytic efficiency of alcohol molecules on its surface …”
Section: Resultsmentioning
confidence: 99%
“…The electron structure of the palladium atom can be changed by doping, and the catalytic efficiency can be improved by the synergistic effect of the two elements . At present, commonly used doping atoms are Au, Cr, Fe, Co, H, C, N, S, and P. Among them, the doping of phosphorus atoms shows its unique charm. The phosphorus atom is a kind of small radius atom, which usually enters the lattice gap of palladium after doping into the palladium nanocatalysts, thus changing the arrangement of palladium atoms from a crystalline structure to an amorphous structure . This structural change can effectively change the adsorption energy of palladium atoms to the intermediate products of catalytic reaction, which can improve the electrocatalytic efficiency .…”
Section: Introductionmentioning
confidence: 99%
“…CO‐stripping experiments are performed to examine the poisoning tolerance of the catalysts to intermediates (Figure 3d). The L‐PdP NA shows the most negative stripping peak potential (0.779 V) and onset potential (0.629 V), since the tensile surface strain facilitates the OH adsorption during the removal of an adsorbed acetyl group, thus promoting the oxidation of CO. [ 8,32 ]…”
Section: Resultsmentioning
confidence: 99%